(untitled) (The Peerian Journal, 2022)
A question of choice of fingers. The problem of fingering is one of the most difficult in piano pedagogy. In connection with the rapid development of musical literature, views in this area are constantly changing: the most unshakable principles of fingering are being criticized, new assumptions are emerging on the rationalization of existing fingering systems